The Effects of Sidt2 on the Inflammatory Pathway in Mouse Mesangial Cells - Hui Sun; Jia-ming Ding; Hui-hao Zheng; Kang-jia Lv; Yun-fei Hu; Ying-hui Luo; Xue Wu; Wen-jun Pei; Li-zhuo Wang; Ming-cai Wu; Yao Zhang; Jia-lin Gao (Hindawi Limited, 2020)
In patients with chronic kidney disease, the abnormal activation of inflammatory pathways is usually an important factor leading to renal fibrosis and further deterioration of renal function. Finding effective intervention targets of the inflammatory signaling pathway is an important way to treat chronic kidney disease. As a newly discovered lysosomal membrane protein, the correlation between SID1 transmembrane family member 2 (Sidt2) and the inflammatory signaling pathway has not been reported. The aim of this study was to investigate the effect of Sidt2 on inflammation by inhibiting the expression of the Sidt2 gene in a mouse mesangial cell line mediated by a lentiviral CRISPR/Cas9 vector. Hematoxylin and eosin staining and microscopy found that the mesangial cells lost their normal morphology after inhibiting the expression of Sidt2, showing that the cell body became smaller, the edge between the cells was unclear, and part of the nucleus was pyknotic and fragmented, appearing blue-black. The expressions of IKK β, p-IKK α/β, NF-κB p65, p-NF-κB p65, p-IκBα, IκBα, and TNF-α in the NF-κB pathway of the Sidt2-/- group were higher than those of the Sidt2+/+ group. p-Jak2 and IL6 increased in the Jak/Stat pathway, and p-ERK and p-P38 increased in the MAPK pathway. The expressions of IKK β, p-IKK α/β, NF-κB p65, p-NF-κB p65, p-IκBα, IκBα, and TNF-α in the NF-κB pathway of the Sidt2+/++LPS group were significantly higher than those in the Sidt2+/+ group. The expressions of IKK β, p-IKK α/β, NF-κB p65, p-NF-κB p65, p-IκBα, IκBα, and TNF-α in the Sidt2-/-+LPS group were higher than those in the Sidt2-/- group. The expressions of p-IKK α/β, NF-κB p65, p-NF-κB p65, p-IκBα, IκBα, and TNF-α in the Sidt2-/-+LPS group were higher than those in the Sidt2+/++LPS group. In the Jak/Stat pathway, the protein expressions of p-Jak2 and IL6 in the Sidt2+/++LPS group were higher than those in the Sidt2+/+ group. The expressions of p-Jak2 and IL6 in the Sidt2-/-+LPS group were higher than those in the Sidt2-/- group. The expressions of p-Jak2 and IL6 in the Sidt2-/-+LPS group were higher than those in the Sidt2+/++LPS group. The expressions of p-JNK, p-ERK, p-P38, and ERK in the MAPK pathway in the Sidt2+/++LPS group were higher than those in the Sidt2+/+ group. The expressions of p-JNK, p-ERK, p-P38, and ERK in the Sidt2-/-+LPS group were higher than those in the Sidt2-/- group. The expressions of p-JNK, p-ERK, p-P38, and ERK in the Sidt2-/-+LPS group were higher than those in the Sidt2+/++LPS group. These data suggested that deletion of the Sidt2 gene changed the three inflammatory signal pathways, eventually leading to the damage of glomerular mesangial cells in mice.